Congenital cerebral palsy: genetic cause and nosological integrity - P. I. Sokolov; N. V. Chebanenko; V. P. Zykov; I. V. Kanivets; A. G. Prityko; P. A. Romanov (Русский журнал детской неврологии, 2021)
The review provides an analysis of 73 full-text articles, the source of which was the Medline, OMIM, NCBI, Pubmed, Scopus, eLibrary.ru databases. The data of studies of the main pathogenetic mechanisms of the formation of the cerebral palsy (CP) phenotype, such as chromosomal aberrations, copy number variations, single nucleotide polymorphisms, associated with the development of the CP phenotype, are reviewed and analyzed. Epigenetic effects on the genome, as well as the effects of the genome on the mechanisms of epigenomic regulation, are examined in detail. The data on the genetic determinism of concomitant pathology and reactivity to therapeutic tactics are presented. Based on the study of data from numerous studies, the authors draw the following conclusions:1) the pathogenesis of the phenotype of CP includes a large number of genes that determine violations of cellular metabolism, neuroontogenesis, brain resistance to hypoxia, etc;2) genes whose abnormalities form a syndromic pathology are involved in the pathogenesis of CP;3) the multidirectionality and breadth of the effects of the gene pool with the outcome in a syndrome-specific distinctive picture of the CP allows us to propose the concept of a neurotropic genome;4) the mechanisms of gene involvement can vary from aberrations to epigenetic imbalances;5) different groups of genes can differentially influence the formation of individual syndromes in the phenotype of CP;6) there are data indicating a genetic determinism of the tendency to contracture, pharmacoreactivity to drugs that reduce muscle tone, reactivity to habilitation effects;7) genomic-epigenomic interactions normally ensure the body’s adaptation to environmental conditions, and with pathology, they increase the likelihood of regulatory breakdowns that lead to the formation of a CP phenotype;8) the exclusion from the diagnosis of CP of genetically determined cases of phenotype development is incorrect.The authors present two anthropogenic reasons for the increase in the frequency of occurrence of de novo identified gene abnormalities:1) anthropogenic impact on the environment, increasing the number of anomalies of the genome de novo; 2) iatrogenic effects of technologies for preserving life, vitality and reproductive ability of carriers of genomic anomalies. This effect leads to the fixation of anomalies in the genome of the population.A paradox is formulated, according to which, in the presence of technologies capable of preserving the life of carriers of genomic anomalies, in vivo technologies for genome correction are only just beginning to be put into practice. Based on this, it is concluded that it is necessary to intensify the development of methods for prenatal diagnosis and gene therapy of CP.